2006
DOI: 10.1258/135763306776084419
|View full text |Cite
|
Sign up to set email alerts
|

Two years' experience with Web-based teleconsulting in dermatology

Abstract: A non-commercial teledermatology network based on store-and-forward operation was established in April 2002. The aim was to create an easy-to-use platform for teleconsultation services, where physicians could seek diagnostic advice in dermatology from a pool of expert consultants and where they could present and discuss challenging dermatology cases with special emphasis on diagnosis and therapy. An online moderated discussion forum was added in October 2003. During the first two years, 348 health-care profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Macro images, the standard method used in most teledermatology settings at the onset of the study, [15][16][17][18][19][20] and PLD images were obtained for each lesion. Two macro images (distance and close-up; digital Nikon Coolpix 4500 with a Nikon SL-1 ring flash [Nikon, Melville, NY]) were obtained of each lesion.…”
Section: Photographsmentioning
confidence: 99%
“…Macro images, the standard method used in most teledermatology settings at the onset of the study, [15][16][17][18][19][20] and PLD images were obtained for each lesion. Two macro images (distance and close-up; digital Nikon Coolpix 4500 with a Nikon SL-1 ring flash [Nikon, Melville, NY]) were obtained of each lesion.…”
Section: Photographsmentioning
confidence: 99%
“…It has previously been demonstrated [1] that open-access teledermatology may serve as a successful platform [9,10] for challenging dermoscopic cases, where advice on diagnosis and therapy can be provided. This is emphasized by the fact that past studies have shown a high diagnostic concordance between telediagnosis and face-toface diagnosis for pigmented lesions [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…120 With the advent of the Internet, digital photography, especially when it relates to digital dermatoscopic features, allows for consultations with specialists and can be utilized for accurate identification of the lesion when referring to a surgeon. [125][126][127][128] An increasing body of evidence supports the utility of total body digital photography. In 18 patients followed up for diagnostically uncertain melanocytic proliferations, Rivers et al 129 attributed early detection of melanomas to changes seen from baseline photographs.…”
Section: Photographymentioning
confidence: 99%